2006
DOI: 10.1080/00207450500514334
|View full text |Cite
|
Sign up to set email alerts
|

Can the Mmpi-2 Discriminate Between Mild-Moderate Tbi and Other Neurologic and Psychiatric Populations?

Abstract: MMPI-2 maintains an extensive empirical base with psychiatric populations, although more recently, neurologically compromised patients have documented unique elevation patterns. This study examined mild-moderate TBI patients, Alzheimer's Dementia patients, and Psychiatric controls on MMPI-2 scales. Participants included 160 outpatients (TBI n = 26, AD n = 74, Psychiatric n = 60). Controlling for family-wise-error, five ANCOVAs were conducted on five MMPI-2 scales, correcting for age and education. TBI and Psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In another study with the PAI, a group of 95 patients with TBI showed elevations in Somatic Complaints, Depression and Borderline Features with prominent clusters for social isolation/confused thinking and for depression/withdrawal [57]. Using the Minnesota Multiphasic Personality Inventory-2 (MMPI-2), TBI patients had elevations on scales for Hypochondriasis, Depression and Hysteria with the presence of anxiety suggesting concomitant PTSD [58,59]. Using the NEO-PI for the Five Factor Model, there were only small decreases in Extraversion and Openness when comparing subjects within the first 3 months of TBI and again 12 months post-TBI [60,61].…”
Section: Discussionmentioning
confidence: 97%
“…In another study with the PAI, a group of 95 patients with TBI showed elevations in Somatic Complaints, Depression and Borderline Features with prominent clusters for social isolation/confused thinking and for depression/withdrawal [57]. Using the Minnesota Multiphasic Personality Inventory-2 (MMPI-2), TBI patients had elevations on scales for Hypochondriasis, Depression and Hysteria with the presence of anxiety suggesting concomitant PTSD [58,59]. Using the NEO-PI for the Five Factor Model, there were only small decreases in Extraversion and Openness when comparing subjects within the first 3 months of TBI and again 12 months post-TBI [60,61].…”
Section: Discussionmentioning
confidence: 97%
“…However, individuals with TBI were not included in this sample. Research with TBI patient groups has consistently shown elevated Hypochondriasis, Depression, Psychasthenia, Schizophrenia, and Hysteria scales (Cattelani et al 1996;Foley et al 2006;Gass 2000;Rohling 2002). These findings are concerning.…”
Section: Meta-analytic Studies Have Proven That No Mild Tbi Patients mentioning
confidence: 97%
“…The dearth of control groups was unexpected, because in TBI studies, psychopathology is so often assessed with the MMPI-2 (Arbisi & Ben-Porath, 1999). Of the studies with control groups, two used neurologic controls (Foley, Garcia, Harris, Golden, & Todd, 2006;Golden & Golden, 2003a) and one did not specify the control group's characteristics (Solbakk et al, 2005); this left too few appropriate control groups for meta-analytic comparison.…”
Section: Data Selectionmentioning
confidence: 99%